2020
DOI: 10.1002/ccr3.3473
|View full text |Cite
|
Sign up to set email alerts
|

Pretilachlor poisoning: A rare case of a herbicide masquerading as organophosphate toxicity

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…A number of chemicals are commonly used for weed management in agriculture, because of their speed and efficiency. Unfortunately, the synthetic herbicides are poisonous to human health and biodiversity [ 1 , 2 ]. They are directly toxic to farmers and indirectly accumulated in agricultural products [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of chemicals are commonly used for weed management in agriculture, because of their speed and efficiency. Unfortunately, the synthetic herbicides are poisonous to human health and biodiversity [ 1 , 2 ]. They are directly toxic to farmers and indirectly accumulated in agricultural products [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have presented six confirmed cases of pretilachlor ingestion and treated in line with OP poisoning. This is not uncommon in our region, as patients often treated for OP poisoning actually ingest chloroacetanilide products with symptoms similar to those of OP poisoning [ 4 ]. While OP poisoning is commonly encountered in the ER and is one of the leading unnatural causes (suicide) of death in Nepal [ 6 ], very few studies have reported pretilachlor poisoning in our part of the world [ 1 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged use of these herbicides has likely cancer-causing consequences [ 3 ]. Pretilachlor’s acute toxicity after ingestion can be mistaken for organophosphate pesticide toxicity, which can lead to improper patient management because these patients frequently exhibit the signs and symptoms of organophosphate toxicity, such as lacrimation, nausea, vomiting, and bladder and bowel incontinence [ 4 ]. Tachycardia, hypotension, sweating, and muscular spasms are seen.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the toxiferous nature of pretilachlor, it was revealed that residues of pretilachlor were detected in water, soil, and crops and were proved fatal for the aquatic as well as terrestrial ecosystems. A case of acute oral intoxication of pretilachlor in humans showed that pretilachlor ingestion resulted in clinical manifestations (Shilpakar et al, 2020). Thus, it is important to study the effect of pretilachlor on nontarget organisms such as cyanobacteria, earthworm, fish, aquatic plants, and other organisms (Mishra & Pabbi, 2004).…”
Section: Pretilachlor-assisted Phytoalexin Accumulation In Plantsmentioning
confidence: 99%